HUBUNGAN KADAR HEMOGLOBIN DENGAN JUMLAH TROMBOSIT PADA PASIEN DEMAM BERDARAH DENGUE - Patandianan, Restiayuh (Universitas Sam Ratulangi, 2013)
Abstract : Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and transmitted by Aedes mosquitoes. DHF affects children tend to further increase the morbidity and mortality that needed more attention, both clinical symptoms and laboratory results. In laboratory hemoglobin levels and platelet counts normal weight changes corresponding degree of illness. This research was an analytic retrospective with a cross-sectional. Data sources were secondary data from medical records at BLU RSUP Prof. Dr. R. D. Kandou Manado. Samples were obtained 56 patients who met the inclusion criteria DHF of the total population sample of 137 patients. The results of the data obtained is then processed into statistical data using parametric test (Pearson test) for found the relationship between hemoglobin levels with platelet counts with Î± = 0,05. . It was found that there was no relationship between hemoglobin levels with platelet counts (p=0,097). Conclusion In this study there was no significant correlation between hemoglobin levels with platelet counts in DHF.Keywords: dengue hemorrhagic fever, hemoglobin levels, platelet counts.Abstrak: Demam berdarah dengue merupakan penyakit infeksi yang disebabkan oleh virus dengue dan ditularkan oleh nyamuk Aedes. DBD yang menyerang anak-anak cenderung lebih meningkatkan morbiditas dan mortalitas sehingga diperlukan perhatian lebih, baik pada gejala klinis maupun hasil laboratorium. Pada pemeriksaan laboratorium kadar hemoglobin dan jumlah trombosit biasa mengalami perubahan. Penelitian ini bersifat analitik retrospektif dengan pendekatan cross sectional. Sumber data merupakan data sekunder dari rekam medik Depertemen Ilmu Kesehatan Anak di BLU RSUP Prof. Dr. R. D Kandou Manado. Sampel penilitian diperoleh 56 pasien DBD yang memenuhi kriteria inklusi dari total populasi sampel 137 pasien. Hasil penelitian diuji menggunakan uji parametrik (Uji Pearson), untuk mengetahui hubungan kadar hemoglobin dengan jumlah trombosit dengan Î± = 0,05. Uji Pearson menunjukkan tidak ada hubungan antara kadar hemoglobin dengan jumlah trombosit (p=0,097). Disimpulkan bahwa tidak ada hubungan antara kadar hemoglobin dengan jumlah trombosit.Kata Kunci: demam berdarah dengue, hemoglobin, trombosit